Cross-Cultural Differences and Psychometric Properties of the Japanese Actions and Feelings Questionnaire (J-AFQ) - Huggins, Charlotte F.; Cameron, Isobel M.; Scott, Neil W.; Williams, Justin H. G.; Yoshikawa, Sakiko; Sato, Wataru (Frontiers in Psychology, 2021)
Aims: We aimed to assess the psychometric properties of a Japanese version of the Actions and Feelings Questionnaire (J-AFQ), an 18-item self-report measure of non-verbal emotional communication, as well as to examine its transcultural properties. Methods: The J-AFQ was administered to 500 Japanese adults (age 20 – 49, 250 male), alongside the Japanese Broad Autism Phenotype Questionnaire (BAPQ-J) and Empathy Quotient (EQ-J). These were compared to a group of 597 British and Irish participants (age 16 – 18, 148 male). J-AFQ was assessed in terms of validity by confirmatory factor analysis and convergence with BAPQ-J and EQ-J using Pearson correlation. Internal consistency and differential item functioning (DIF) were assessed and compared between Japanese and UK/Irish participants. Results: Reversed worded items (RWIs) showed poor item-total correlations but excluding these left a 13-item version of the J-AFQ with good internal consistency and content validity. Consistent with the English version, J-AFQ scores correlated with EQ and lower BAPQ scores. However, comparing across cultures, J-AFQ scores were significantly lower in the Japanese sample, and there was evidence of important DIF by country in over half of the J-AFQ items Conclusion: Cultural differences in attitudes to self-report, as well as increased acquiescence to RWI’s also seen in previous studies, limit the value of the 18-item instrument in Japanese culture. However, the 13-item J-AFQ is a valid and reliable measure of motor empathy, which, alongside the English version, offers promise for research in motor cognition and non-verbal emotional communication across cultures.